Analisis Afiks Pada Lirik Lagu Anggi Marito Dalam Album Tak Segampang Itu - Syahbana, Sultan Ali; Siagian, Irwan (Peneliti.net, 2023)
The purpose of this study is to explain the use of affixes in the lyrics of 'Anggi Marito' in the album 'Tak Segampang Itu'. The aim of this study is to improve our understanding of fixation. This study was carried out by qualitative method. The subject of this investigation was the use of affixes in the lyrics of